A fast simulation tool for ship grounding damage analysis. (15th October 2022) - Pineau, Jean-Philippe; Conti, Fabien; Le Sourne, Hervé; Looten, Thibaut
Abstract: This paper presents a numerical tool based on analytical formulations for rapid assessment of damage in ship grounding accidents. Through a step-by-step solution, the ship resistant force is assessed by the super-element method and transferred to a 6-DoF external dynamics solver, which updates the global ship motion by taking into account the action of hydrodynamic forces. The two-way coupled solver is first confronted to finite element simulations considering a 34-kTons cruise ship in bottom and side grounding situations. It is then used to simulate thousands of scenarios, varying the rock shape, the ship impact location, initial penetration and velocity as well as rock/hull friction coefficient. In this way, the influence of ship structural properties (shell thickness, material grade, etc.) on the breach size is investigated. The highest breach reductions are obtained by increasing either the outer shell thickness or the material grade, while acting on transverse frames marginally affects the damage extent. It also appears that a bottom impact is systematically more damaging than a side impact, all else being equal. Likewise, a structural reinforcement is demonstrated to be more efficient in bottom grounding than in side grounding. This is because in side grounding situation, the ship is pushed away by rock and thus undergoes significant sway, yaw and sometimes roll motions that limit the damage extent. Finally, friction is shown to be of primary importance in bottom grounding, while its effect is rather limited in side grounding. Highlights: A simplified tool based on analytical formulations is proposed for ship grounding damage assessment. Parametric analysis is performed to investigate the effect of parameters on the damage extent. extent. Outer shell and girders are shown to absorb the main part of the energy. It is shown that bottom grounding is systematically more damaging than a side impact. For side grounding accident, the ship escapes from the rock due to large sway and yaw motions.